Jaw malformation of hatchery reared golden pompano Trachinotus ovatus (Linnaeus 1758) larvae. (26th August 2014) - Ma, Zhenhua; Zheng, Panlong; Guo, Huayang; Zhang, Nan; Jiang, Shigui; Zhang, Dianchang; Qin, Jian G
Abstract: Jaw malformations of hatchery reared golden pompano Trachinotus ovatus larvae were studied from 1 day post hatch (DPH) to 31 DPH. The severity of jaw deformities was classified into three levels where '0' represents normal jaw; '1' is intermediate jaw malformation; and '2' is severe jaw malformation. The severe jaw malformations of golden pompano larvae were clearly observed on 3 DPH. Starting from 3 DPH, both intermediate and severe jaw malformations were observed and the total incidence of jaw malformations ranged from 9.6% to 46.6%. The highest severe jaw malformation occurred on 5 DPH, and 25% larvae exhibited serve jaw malformation. On 11 DPH, jaw malformations reached the peak with 46.6% fish exhibiting jaw malformations of either category 1 or 2. On 26 DPH, the percentage of intermediate jaw malformation reached the peak value (36.4%). This was the first study reporting jaw malformation of golden pompano larvae, and the result can be used as a reference point for future research on the control of jaw malformation in golden pompano.